Ethics and values for engineers and managers - Chattopadhyay,Subrata (Himalaya Pub. House, 2014)
Ethics and values for engineers and managers / Chattopadhyay,Subrata. -- Kolkata: Himalaya Pub. House, 2014 174.4 C495 No. of Copies : 1